Protective Effect of Chrysanthemum morifolium cv. Fubaiju Hot-Water Extracts Against ARPE-19 Cell Oxidative Damage by Activating PI3K/Akt-Mediated Nrf2/HO-1 Signaling Pathway - Hao, Yiming; Li, Yanfang; Liu, Jie; Wang, Ziyuan; Gao, Boyan; Zhang, Yaqiong; Wang, Jing (Frontiers in Nutrition, 2021)
Chrysanthemum morifolium cv. Fubaiju is a kind of widely-consumed herb tea with multi-health benefits. The present study was aimed to evaluate the protective capacity of Fubaiju hot-water extracts (CM) against ARPE-19 cells oxidative damage. The results showed that pretreatment with 100 μg/mL CM could significantly reduce cell oxidative damage and apoptosis. Pro-apoptotic protein expression such as Bax, cleaved caspase-3 and cleaved PARP was significantly decreased after CM addition, while the expression level of antioxidant enzyme including Catalase, GCLc, SOD2 and NQO-1 was significantly promoted. Meanwhile, CM treatment upregulated Akt phosphorylation, Nrf2 nuclear translocation and the expression level of antioxidant gene HO-1 in a dose-dependent manner under oxidative stress. Knockdown of Nrf2 by targeted siRNA alleviated CM mediated HO-1 transcription, and almost abolished CM-mediated protection against H2O2-induced cells damage. Correspondingly, the protective effect of CM was dramatically blocked after interference with PI3K/Akt inhibitor LY294002, indicating the protective effect of CM on cells oxidative damage was attributed to PI3K/Akt-mediated Nrf2/HO-1 signaling pathway.